Impact Of Maternal Anemia On Perinatal Outcomes: A Prospective Study. - Haroon, Asma; Hameed, Aisha; Zulfiqar, Irsa; Memon, Farzana Rahim; Ejaz, Maryam; Anwar, Muhammad Ijaz (Journal of Neonatal Surgery, 2025)
Background: Anemia in pregnancy is still a major public health problem in developing countries and plays an important role in adverse perinatal outcomes. The low hemoglobin levels reduce oxygen delivery to the fetus and has complications such as intrauterine growth restriction, preterm birth and perinatal morbidity. Early diagnosis and treatment are necessary for better maternal and neonatal outcomes. Objective: To ascertain the effects of maternal anemia on perinatal outcomes such as birth weight, preterm delivery and neonatal morbidities in pregnant mothers receiving care at the tertiary level hospitals. Study design: A prospective study at Watim General Hospital from Jan 2024 to December 2024. Methods: This is a prospective study of 100 pregnant women. Hb was determined with standard laboratory methods and categorized according to WHO criteria. Maternal characteristics, obstetric history, and neonatal outcomes were extracted. Continuous variables were presented as the mean ± SD. Chi square and t-tests were used to compare outcomes among anemic versus non-anemic subjects. All analyses were performed by SPSS version 24.0 and p<0.05 was considered as the level of significance. Results: The mean maternal age was 27.4 ± 4.6 years in a cohort of 100 subjects. Anemia prevalence was 52%. The frequency of low birth weight was 46% as against 21% among anemic and non-anemic mothers respectively (p=0.01). Anemic women had significantly more preterm deliveries (33% vs. 12%, p=0.02). Twenty nine percent of anemic mother's babies versus 10% in the nonanemic group needed to be admitted to NICU (p=0.01). Perinatal mortality were also significantly higher in the anemic group (8% vs. 2%, p=0.04), reflecting a clear relationship between maternal anemia and adverse perinatal outcomes. Conclusion: Maternal anemia was significantly associated with higher odds of adverse perinatal outcomes including low birth weight, preterm birth, admission to NICU and perinatal mortality. These results underscore the demand for antenatal screening and correct intervention of anemia in order to enhance maternal and neonatal survival. Public health measures emphasizing prevention, early diagnosis and nutrition supplementation are vital in decreasing anemia related perinatal morbidity and mortality